Patient choice and choice fees in the Portuguese National Health System - Matos, João Henrique Ramos Rola Fidalgo de (2012)
This work aims to assess the possibility of allowing patients the freedom of choice in the Portuguese National Health System (NHS). Patient choice has been promoted on several countries to reduce waiting times and to encourage competition between providers. This study also tries to identify the likelihood of implementing a fee associated with choice (choice fee) to generate an additional source of income, which would be an innovative measure. The research focuses on similar health systems such as the United Kingdom (UK) that recently implemented this choice policy, which effectively spurred competition and improved economic efficiency, quality and equity. Price-sensitivity and user fees are also studied to assess the applicability of the choice fees, since there are no studies comprising fees associated with patient choice. Therefore, the mains objectives of this study were to explore patients’ reactions to the offer of provider choice and to determine which factors influenced their decisions on where to have their treatment; to compare uptake of choice between different social groups; and to evaluate the feasibility of applying a fee in order to choose, as well as what would be the best-fit value for the choice fees. A questionnaire was created for such purposes, and was then made available online to target a wide set of patients, and printed for personal interviews in a health center. The results were processed statistically and econometric models were estimated using an ordered probit approach. Important results include the fact that patients consider clinical outcomes such as waiting times the most important factors in providers and practical considerations such as distance and type of hospital as the least important, indicating that choice would create significant pressure for hospitals to improve outcomes if they want to be chosen. Also, the majority finds choice to be more important than the associated price, indicating willingness to pay and inexistence of a great asymmetry in social groups hence creating the necessary conditions for the choice fees. Concerning the best-fit value, the minimum proposed in this study would be the appropriate fee to be implemented for this sample, which represents a value that is equivalent to the user fee. Although this study had as limitations the size and composition of the sample, it provides useful insights into how choices would be made due to the rich structure of the variables that contributed to the construction of the econometric models, and provides the basis for future research to be conducted on a much broader sample.